2005
DOI: 10.1136/jnnp.2004.039818
|View full text |Cite
|
Sign up to set email alerts
|

The cerebral correlates of different types of perseveration in the Wisconsin Card Sorting Test

Abstract: Objectives: To explore the neural substrates corresponding to the perseverative errors in the Wisconsin Card Sorting Test (WCST). Methods: The study examined the correlations between the WCST performances and the SPECT measurements of regional cerebral blood flow (rCBF) in subjects with neurodegenerative dementia. Negative non-linear correlations between the rCBF and the two different types of the perseverative errors (''stuck-in-set'' and ''recurrent'' perseverative errors) were calculated on a voxel basis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 66 publications
3
46
1
4
Order By: Relevance
“…The regression analyses revealed that the set-switching factor observed in 7-year-olds was predicted by Shifting (as expected) and the set-maintenance factor by Inhibition (as expected). The finding that Shifting contributed to WCST performance is in accordance with previous studies showing that the ability to flexibly shift between tasks contributes to WCST performance (e.g., Miyake et al, 2000;Nagahama et al, 2005). The finding that Inhibition is a good predictor of the set-maintenance factor is in accordance with theories assuming that young children are more susceptible to interfer-DEVELOPMENT OF SET-SWITCHING AND SET-MAINTENANCE ON THE WCST ence from irrelevant information (e.g., Dempster, 1992;Ridderinkhof & Van der Molen, 1995; for reviews, see also Kipp, 2005;Van der Molen, 2000).…”
Section: Contribution Of Ef Component Processes To Wcst Performancesupporting
confidence: 82%
See 1 more Smart Citation
“…The regression analyses revealed that the set-switching factor observed in 7-year-olds was predicted by Shifting (as expected) and the set-maintenance factor by Inhibition (as expected). The finding that Shifting contributed to WCST performance is in accordance with previous studies showing that the ability to flexibly shift between tasks contributes to WCST performance (e.g., Miyake et al, 2000;Nagahama et al, 2005). The finding that Inhibition is a good predictor of the set-maintenance factor is in accordance with theories assuming that young children are more susceptible to interfer-DEVELOPMENT OF SET-SWITCHING AND SET-MAINTENANCE ON THE WCST ence from irrelevant information (e.g., Dempster, 1992;Ridderinkhof & Van der Molen, 1995; for reviews, see also Kipp, 2005;Van der Molen, 2000).…”
Section: Contribution Of Ef Component Processes To Wcst Performancesupporting
confidence: 82%
“…In addition, we examined the relative contribution of different EF components during development. More specifically, in common with previous studies (e.g., Miyake et al, 2000;Nagahama et al, 2005), we expected that, with advancing age, Shifting plays a significant role in set-switching during WCST performance. Our prediction was based on studies of PFC patients, who show deficient set-maintenance abilities on the WCST.…”
Section: Present Studysupporting
confidence: 56%
“…Barcelo et al, 1997;Barcelo & Santome-Calleja, 2000;Drewe, 1974;Stuss & Benson, 1984). Recent neuroimaging studies also suggest that overcoming perseverative tendencies correlates with activity in prefrontal regions (Nagahama, Okina, Suzuki, Nabatame, & Matsuda, 2005).…”
Section: Learned Irrelevance and A Visual Learning Paradigmmentioning
confidence: 99%
“…Alguns métodos de avaliação cognitiva permitem discriminar com maior acurácia a presença de perserveração na triagem e testagem neuropsicológica. A teste de Wisconsin de classificação de cartas (Wisconsin Card Sorting Test) tem sido extensamente utilizado como meio de discriminar a flexibilidade cognitiva, ou seja, a capacidade de modificar o conjunto de habilidades cognitivas necessárias a compreensão da percepção de um estímulo visual complexo para outro 13 . A correlação de achados de fenômenos de perseveração neste teste foi fortemente correlacionada a presença de disfunção frontal em exames de neuroimagem 13 .…”
Section: Discussionunclassified
“…A teste de Wisconsin de classificação de cartas (Wisconsin Card Sorting Test) tem sido extensamente utilizado como meio de discriminar a flexibilidade cognitiva, ou seja, a capacidade de modificar o conjunto de habilidades cognitivas necessárias a compreensão da percepção de um estímulo visual complexo para outro 13 . A correlação de achados de fenômenos de perseveração neste teste foi fortemente correlacionada a presença de disfunção frontal em exames de neuroimagem 13 . O teste do desenho do relógio, frequentemente empregado como método de triagem cognitiva, também permite identificar comportamentos perseverativos, associados por exemplo a repetição da utilização do mesmo número na construção do relógio.…”
Section: Discussionunclassified